Summary of the best evidence for non-pharmaceutical interventions for mild cognitive impairment in Parkinson’s disease - Liu, Yud Dan; Li, Hui Fang; Zhai, Ya Xian; Shen, Yun Xia; Yang, Jinmei; He, Li Mei; Shen, Ting (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to synthesize and evaluate the best evidence for non-pharmacological interventions targeting mild cognitive impairment in Parkinson’s disease (PD-MCI), thereby informing the development of cognitive management strategies for this population.MethodsA systematic search was conducted across multiple databases (e.g., UpToDate, BMJ Best Practice, and Cochrane Library) up to November 2024. Two researchers independently screened literature, assessed quality using standardized tools (AGREE II, JBI criteria), and graded evidence.ResultsThirteen studies were included (five guidelines, two clinical decisions, two systematic reviews, one meta-analysis, and three RCTs). Twenty evidence points were categorized into six themes: safety/efficacy, assessment, cognitive training, exercise, health education, and multi-strategy approaches.ConclusionThis study consolidates evidence supporting non-pharmacological interventions for PD-MCI, offering actionable recommendations for clinical practice to delay progression to Parkinson’s disease dementia (PDD).